2019
DOI: 10.1128/iai.00739-18
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 3–TRIF Pathway Activation by Neospora caninum RNA Enhances Infection Control in Mice

Abstract: Neospora caninum is a protozoan parasite closely related to Toxoplasma gondii and has been studied for causing neuromuscular disease in dogs and abortions in cattle. It is recognized as one of the main transmissible causes of reproductive failure in cattle and consequent economic losses to the sector. In that sense, this study aimed to evaluate the role of Toll-like receptor 3 (TLR3)-TRIF-dependent resistance against N. caninum infection in mice. We observed that TLR3 Ϫ/Ϫ and TRIF Ϫ/Ϫ mice presented higher par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
1
13
1
Order By: Relevance
“…Despite this discrepancy, other aspects of those studies (51,56) are consistent with our results. For one, our data clearly show increased susceptibility to N. caninum in MyD88 knockout mice based on higher parasite burdens at the later stages of acute infection ( Fig.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Despite this discrepancy, other aspects of those studies (51,56) are consistent with our results. For one, our data clearly show increased susceptibility to N. caninum in MyD88 knockout mice based on higher parasite burdens at the later stages of acute infection ( Fig.…”
Section: Discussionsupporting
confidence: 92%
“…due to the higher effective inoculum (10 6 trypan blue-negative parasites versus 10 6 total tachyzoites in the present study). Differences in inocula and parasite strains may also contribute to the differences between the present study and another showing that TLR3 knockout mice were more susceptible to N. caninum than were WT mice (in this case after infection with 10 7 tachyzoites [56]). In our study, we observed small differences in parasite burdens and IFN-␥ levels at 4 hpi and no impact on parasite control in TLR3 Ϫ/Ϫ mice, as N. caninum infections were controlled within the same time frame as in WT mice.…”
Section: Discussioncontrasting
confidence: 62%
See 2 more Smart Citations
“…MyD88-dependent TLR signaling has been reported to play a key role in parasite recognition and induction of suitable immune response against this parasite (Mineo et al, 2009(Mineo et al, , 2010Beiting et al, 2014;Gurung and Kanneganti, 2016). However, activation of MyD88-independent TLR pathways, such as the TRIFdependent TLR3 signaling, are also important for activation of the immune response against N. caninum, as potent inducers of type I interferons (Beiting et al, 2014;Miranda et al, 2019). In parallel, NLRs have also emerged as important components of the innate immune system, due to its ability to recognize and eliminate intracellular parasites (Zamboni and Lima-Junior, 2015;Coutermarsh-Ott et al, 2016).…”
Section: Discussionmentioning
confidence: 99%